Training needs assessment of academic archivists in Iloilo City - Alenzuela, Reysa; Gonzales, Grace Marie B.; Granda, Yolanda C.; Montesa, Teresa S. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
This study surveyed administrators and archives personnel of academic institutions in Iloilo City in order to assess their training needs and to recommend modules for training in archives administration. Administrators and archives personnel from 22 colleges and 5 universities were made respondents in the study. Eight of these institutions have established their archives while the rest numbering 18, have plans to establish one in their institutions. Although there may be other reasons why majority of these institutions do not have established archives, this study focused on the lack of training and education by administrators and archives personnel as one factor affecting the development of a sound archives program in the city. The data in this study showed that there was inadequate training undertaken by people involved in the establishment and administration of archives. This inadequacy of training opportunity was because the provision of archives education programs was few or not available. In the opinion of administrators, archives education was not available or was inadequate. Forty-six and forty three percent (46.43) of them believed that there were no existing organization which promote archives education and training, thirty-two and fourteen percent (32.14) were not aware of any training conducted in the city and twenty-one and forty-three (21.43) percent said that no such archives education was being held. The opinions of administrators were confirmed by the archives personnel surveyed.
Thirty-three and thirty-three percent (33.33) of the archivists propounded that continuing education programs were inadequate while sixty-six and sixty-six percent (66.66) said that it was mostly unavailable. The findings of the study concluded that there was a need to promote awareness of archives education in Iloilo City. The study probed into how the archival training would be affected in academic institutions in Iloilo City. In order to determine their needs, the personal data or profile of administrators and archives personnel, previous training they have attended, including the time of taking the training, and the mode of archives education they have taken were analyzed. Part of the questionnaire also probed into the preferences of the respondents with regard to the training mode of archives education. The study revealed that the archives education most preferred by respondents was seminar-workshops. Other modes which were found desirable were conferences/conventions, symposia/fora, and distance education. As regards the preferred topics of the respondents vis-a-vis their educational background, the following were most preferred: Records management, Arrangement and Description, Preservation and Restoration, Reference, Access and Security, Archives Concepts, Principles and Practices. The contents of the training modules prepared were partly based on the preferred topics while the design of the modules was based on other considerations, such as the level of knowledge and skills, and work responsibilities of the respondents Based on the survey data, the researcher prepared modules for formal and non-formal archives education. These modules were recommended subject to review by organizations which are conducting training in archives with due respect to the expertise of their leaders.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Archivists -- Philippines -- Iloilo City; Archivists -- In-service training -- Philippines -- Iloilo City; Training needs -- Philippines -- Iloilo City; Needs assessment -- Philippines -- Iloilo City